The Color of paradise - Majidi, Majid, 1959-; Ramaz\0324ani, Muhsin; Mahjub, Hossein; Feiza, Salime; Varahonar Film Company; Sony Pictures Classics (Firm); Columbia TriStar Home Video (Firm) ([Tehran, Iran : Varahonar Film Co.] ; Culver City, CA : Distributed by Columbia TriStar Home Entertainment, 1999)
Mohammad joyfully returns to his tiny village on summer vacation from the Institute for the Blind in Tehran, unaware of his father's intention to disown him. Engaged to be married, the widowed man has kept Mohammad a secret from his fiancě, certain the boy's disability will destroy his only chance for happiness. With the wedding swiftly approaching Mohammad's future hangs precariously in the balance as his father struggles against his destiny, unable to see the wonder of life and love that is so clear to his son.
Start -- Braille test -- Souvenirs -- Waiting for father -- Return to the nest -- "Keep this child." -- Business -- Catching the wind -- ABC -- Granny -- Gifts -- Bride-to-be -- The Shrine -- "Make a wish." -- Special guest -- By the sea -- "Where are we going?" -- Ali Fatemi -- A poor, miserable man -- Carpenter's apprentice -- Worried about Hashem -- Delicate touch -- "Take them." -- Granny's funeral -- Marriage canceled -- Going home -- Swept away -- A miracle.
Originally produced as an Iranian motion picture in 1999.
Special features: Majid Majidi talent file; Theatrical trailers [The Color of Paradise and other Sony Pictures Classics features].
[Director of photography Hashem Attar ; camera operator, Mohamad Davoudi ; editor, Hassan Hassandoost ; original music, Ali Reza Kohandiri].
[Mohsen Ramezani (Mohammad), Hossein Mahjub (Hashem, the Father), Salime Feiza (Granny), Farnaz Saffati (Bahareh, big sister), Elham Sharifi (Hanyeh, little sister)].
DVD, Region 1, Dolby Digital 2.0 Stereo, widescreen presentation in original theatrical aspect ratio of 1.85:1.
In Farsi with optional English, French, or Spanish subtitles ; closed-captioned in English.
Keywords: Blind children -- Drama; Parents of children with disabilities -- Drama; Remarriage -- Drama; Feature films; Video recordings for the hearing impaired